Trimerisation of carbon suboxide at a di-titanium centre to form a pyrone ring system12. Issue 22 (16th May 2018) - Tsoureas, Nikolaos; Green, Jennifer C.; Cloke, F. Geoffrey N.; Puschmann, Horst; Roe, S. Mark; Tizzard, Graham
Abstract : Bis(pentalene)dititanium Ti2 (μ:η 5, η 5 -Pn † )2 trimerises carbon suboxide (O{C{C{C{O) to form [Ti2 (μ:η 5, η 5 -Pn † )2 μ-C9 O6 ], which contains a 4-pyrone core, via the monoadduct [Ti2 (μ:η 5, η 5 -Pn † )2 (η 2 -C3 O2 )]. Abstract : The reaction of the syn -bimetallic bis(pentalene)dititanium complex Ti2 (μ:η 5, η 5 -Pn † )2 (Pn † = C8 H4 (1, 4-Si i Pr3 )2 )1 with carbon suboxide (O{C{C{C{O, C3 O2 ) results in trimerisation of the latter and formation of the structurally characterised complex [Ti2 (μ:η 5, η 5 -Pn † )2 μ-C9 O6 ]. The trimeric bridging C9 O6 unit in the latter contains a 4-pyrone core, a key feature of both the hexamer and octamer of carbon suboxide which are formed in the body from trace amounts of C3 O2 and are, for example, potent inhibitors of Na + /K + -ATP-ase. The mechanism of this reaction has been studied in detail by DFT computational studies, which also suggest that the reaction proceeds via the initial formation of a mono-adduct of1 with C3 O2 . Indeed, the carefully controlled reaction of1 with C3 O2 affords [Ti2 (μ:η 5, η 5 -Pn † )2 (η 2 -C3 O2 )], as the first structurally authenticated complex of carbon suboxide.